The Corruption in Religious Text and Local Wisdom Perspectives in Bugis Society - Ismail Suardi Wekke; Muhammad Yusuf (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
Corruption is a detrimental and harmful crime that is done individually or collectively. Therefore, corruption must be prevented and overcome. To prevent the corruption, firstly, the factors that lead the corruption should be eradicated; then, the prevention actions are formulated. This article aims to elaborate the guidance from the Qur’an and the local wisdom from Bugis society investigating the causes of corruption and how the Qur’an offers the prevention action of the corruption. To understand the guidance in the Qur’an and to prevent the corruption, this study was conducted through the Arabic linguistic approach. In addition, the researchers integrated the guidance in the Qur’an with the local wisdom values derived from the Bugis culture relevant to the prevention of corruption. This study shows that the Qur’an commences the prevention of corruption in two ways: the first, it is done through total structural reform; and the second, the analysis is started from the ‘inner side’ of humans based on the concept of nafsun stated in the Qur’an. Culturally, preventing the corruption should always refer to the principles of lempu’, amaccang, agettengeng, asitinajang, reso, and siri’ . Those values should be reinforced and embodied (instilled) in life. In short, the values of local wisdom are needed to be reintroduced and taught, especially to the younger generation before they become leaders in the future.